The Influence of Taxpayer Awareness And Drive-Thru System On The Level of Tax Compliance of Motor Vehicle Taxpayers In Palembang - Destiawan, Destiawan; Erdiansyah, Erdiansyah; Sudiyanto, Totok (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This study aims to examine the effect of taxpayer awareness and the drive-thru system on the tax compliance of motor vehicle taxpayers in Palembang. The research uses a quantitative descriptive approach with a sample of 400 respondents. Data were analyzed using regression tests to assess both partial and simultaneous effects. The results show that taxpayer awareness and the drive-thru system simultaneously have a significant effect on tax compliance. Partially, both taxpayer awareness and the drive-thru system also significantly influence compliance levels. The coefficient of determination indicates that 40.8% of taxpayer compliance is explained by these two variables, while 59.2% is influenced by other factors beyond this study. These findings highlight the importance of increasing taxpayer awareness and optimizing service systems to improve compliance.